Pengaruh Cita Rasa, Harga, Promosi terhadap Keputusan Pembelian di Burjo Bro Kota Surakarta - Theopilus Dwi Prakoso; Sumaryanto Sumaryanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the significance of the influence of taste, price and promotion on purchasing decisions at Burjo Bro, Surakarta city. The types of data used are quantitative data and qualitative data. The data source in this research is primary data using a questionnaire distributed to respondents. The population in this research are all Burjo Bro consumers in Surakarta. The sampling method is purposive sampling or sampling with certain characteristics with a sample size of 100 people. The data analysis methods used are descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2). The results of this research using multiple linear regression analysis show that taste, price and promotion have a significant influence on purchasing decisions at Burjo Bro. The results of the F test calculation have an F count of 77.921 with a p-value of 0.000 < 0.05, so Ho is rejected and Ha is accepted, meaning the model is correct. The coefficient of determination (R2) for this model is 0.700, meaning that the contribution of the independent influence (taste), X2 (price) and X3 (promotion) to Y (purchasing decision) is 42.2%.